PWE-183 Survivin expression increases in the progression to oesophageal adenocarcinoma. (22nd June 2015) - Puccio, I; Butt, MA; Rodriguez-Justo, M; Khan, S-U-R; Sehgal, V; Novelli, M; Lovat, LB; Hamoudi, R
Abstract : Introduction: It has been postulated that the process of apoptosis leads to the development of neoplastic clones with prolonged survival. Survivin, an inhibitor of apoptosis, is an integral to this process. The primary aim of this study is to examine the expression of Survivin in the progression from Barrett's Oesophagus (BO) to oesophageal adenocarcinoma (OAC). Method: Endoscopic biopsies containing the relevant pathologies from 72 patients were immunostained for Survivin expression - normal squamous (Sq) 14, non-dysplastic BE (NDBE) 14, low-grade dysplasia (LGD) 17, high-grade dysplasia (HGD) 17 and oesophageal adenocarcinoma (OAC) 7. Survivin expression was scored by 2 expert GI pathologists using the Allred system (a score comprising both intensity and extent of staining) and analysed using one-way ANOVA with Bonferroni post-hoc analysis to examine the trend between the various groups in the upper GI sequence. Results: Multivariate analysis using one-way ANOVA and Bonferroni post-hoc analysis showed a strongly significant increase in both intensity and extent of Survivin expression in the progression from squamous, through non dysplastic Barrett's oesophagus, low-grade dysplasia, high-grade dysplasia and invasive adenocarcinoma (OAC) p < 0.0001 for both analyses. Allred scores also rose incrementally through the progression sequence, with a mean score of 1.7 in squamous, 2.8 in NDBE, 3.8 in LGD, 5.2 in HGD and 6.1 in cancer (p < 0.0001). Conclusion: This study shows that Survivin expression follows a linear incremental up-regulation in the progression to OAC. This early up-regulation suggests increasingly prominent roles for apoptosis inhibition in this pathway. In addition, the results suggest that inhibitors of Survivin might play a role in the prevention of progression as well as the treatment of OAC. Disclosure of interest: None Declared.